Analysis of Physics of Novel Light-Emitting Diode for Holographic Imaging - Wah, Thae Nu; Win, Thanda; Win, Lei Lei Yin; Hla Myo Tun; Pradhan, Devasis (Journal of Novel Engineering Science and Technology, 2024)
The paper focuses on the analysis of the physics of a novel light-emitting diode for holographic imaging. The research problems in this study are based on the specific challenges that were discussed in the introduction. The solution for this research problem is accomplished with two approaches such as (i) device modeling, physics of LEDs, and characteristics of LEDs under the theoretical analysis and (ii) fabrication of LEDs, PL and FTIR measurement, performance check, and performance comparison under the experimental studies. The specific objectives of this research are to advance the LED design for optical transmission in 5G communication systems, to recognize the semiconductor material for LED structure, and to approach theoretical and numerical calculations for LED. In these analyses, there are two main approaches for solving the performance of the novel light-emitting diodes. The first one is to develop the effective structure for light emitting diode and the other is to develop the energy diagram design of III-V and II-VI compound-based LED. The simulation analyses were carried out with the help of MATLAB language. The results confirm that the numerical analyses of these two developments could be supported to estimate the outcomes of experimental studies without using real equipment in the laboratory.